2019
DOI: 10.1074/jbc.ra119.008902
|View full text |Cite
|
Sign up to set email alerts
|

Tick saliva protein Evasin-3 modulates chemotaxis by disrupting CXCL8 interactions with glycosaminoglycans and CXCR2

Abstract: Chemokines are a group of chemotaxis proteins that regulate cell trafficking and play important roles in immune responses and inflammation. Ticks are blood-sucking parasites that secrete numerous immune-modulatory agents in their saliva to evade host immune responses. Evasin-3 is a small salivary protein that belongs to a class of chemokine-binding proteins isolated from the brown dog tick, Rhipicephalus sanguineus . Evasin-3 has been shown to have a high affinity for chemokines CXCL1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 57 publications
(66 reference statements)
4
27
0
Order By: Relevance
“…In particular, the 'S5' region (between Cys-5 and Cys-6) is highly positively charged in Class B(I) and neutral or negative in Class B(II), potentially contributing to the more restricted chemokine binding profiles of Class B(I) Evasins. Consistent with this proposal, the recent description of EVA-3 (truncated at both N and C termini) docked to CXCL8 [48] showed that the S5 region of EVA-3 interacts with the b1-strand of CXCL8, which explains why binding of EVA-3 disrupts dimerization (and the related glycosaminoglycan binding) of CXCL8. In addition, this docked structure indicated that the regions of EVA-3 close to the N terminus of the b1-strand and the C terminus of the b3-strand bind to a cavity between the a-helix and N-loop/helical turn of CXCL8.…”
Section: Structural Basis Of Chemokine Recognitionsupporting
confidence: 59%
See 1 more Smart Citation
“…In particular, the 'S5' region (between Cys-5 and Cys-6) is highly positively charged in Class B(I) and neutral or negative in Class B(II), potentially contributing to the more restricted chemokine binding profiles of Class B(I) Evasins. Consistent with this proposal, the recent description of EVA-3 (truncated at both N and C termini) docked to CXCL8 [48] showed that the S5 region of EVA-3 interacts with the b1-strand of CXCL8, which explains why binding of EVA-3 disrupts dimerization (and the related glycosaminoglycan binding) of CXCL8. In addition, this docked structure indicated that the regions of EVA-3 close to the N terminus of the b1-strand and the C terminus of the b3-strand bind to a cavity between the a-helix and N-loop/helical turn of CXCL8.…”
Section: Structural Basis Of Chemokine Recognitionsupporting
confidence: 59%
“…The structure of EVA-3 initially shown by Deruaz et al [8] was refined as an asymmetric dimer containing a cystine knot [39]. The protomer structure was recently confirmed by NMR analysis [48]. Each protomer has a 'knottin' cystine knot topology ( Figure 5A-C), consisting of a single layer b-sheet linked by two long loops, with these elements connected by three disulfide bonds, one of which passes through the macrocycle formed by the other two disulfides.…”
Section: Structure Of Eva-3mentioning
confidence: 93%
“…In contrast, the C6 fold Evasin-3 had high affinity for the CXC chemokines CXCL1 and CXCL8 (and their murine related proteins: CXCL1 and CXCL2). Potent anti-inflammatory activity of Evasins has been demonstrated in several in vivo animal models of disease (255,256).…”
Section: Tick Saliva Protein Evasin-3 and Synthetic Variantsmentioning
confidence: 99%
“…Both synthetic Evasin-3 variants showed high affinity for CXCL8, although lower than the affinity of native Evasin-3 for CXCL8. The long NH 2 -and COOHtermini of native Evasin-3 apparently affect the internal dynamics of its structure, resulting in lower K D values (256).…”
Section: Tick Saliva Protein Evasin-3 and Synthetic Variantsmentioning
confidence: 99%
“…Moreover, the administration of recombinant Evasin-1 reduced skin inflammation and decreased mortality in mice deficient in the chemokine receptor D6, which renders then highly susceptible to inflammation (81). Evasin-3 is specific for the CXC chemokines CXCL8 and CXCL1 and was recently found to disrupt the interaction between CXCL8 and glycosaminoglycans and CXCR2 (Figure 2), which modulate neutrophil migration (82). Several studies have demonstrated the effectiveness of Evasin-3 in different neutrophil-dependent disease models.…”
Section: Recruitment Of Blood-borne Innate Immune Cellsmentioning
confidence: 99%